If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -5n = -6n + n Combine like terms: 6n + -5n = 1n 1n = -6n + n Combine like terms: -6n + n = -5n 1n = -5n Solving 1n = -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. 1n + 5n = -5n + 5n Combine like terms: 1n + 5n = 6n 6n = -5n + 5n Combine like terms: -5n + 5n = 0 6n = 0 Divide each side by '6'. n = 0 Simplifying n = 0
| 2x*4-x+7+4x-8-5x^2+2+3x= | | 2/3x-1/3=32/3 | | 2/3x-12=10 | | 30-75=10z-4 | | 9y-7-5y+6=0 | | 6+2(3y-2)=4(1+y) | | d-8=10 | | 4x-x=22-4 | | 12+4q=17+3q | | 51=3+8x | | U=might | | Ak-r=an | | 24/-10-5/-4 | | 3(7+2)=3(7)+3(2) | | 2z^2+9z=5 | | 1.8x+2.8=2.5x+2 | | 4(x+3)-4=8x+10-4 | | 3x+5=4x-6 | | 3.2/3.44 | | 3(x-2)=5x-2x-6 | | m/7=3/5 | | -x-(13+4x)=-3(6-9x)+2 | | w=-10.5+0.5p | | 5m-13m=16 | | 1/3*3.14*4*4*7 | | 9x-2(x-8)=7(x+1)+6 | | 3x-2(x+3)=5x-2x | | Lw=a | | 6-g=2 | | 7-y=3 | | 4x-10y=2+10 | | 3(P-1)=2p+3 |